Evolution of glacial lakes and southernmost GLOFs in the Cordillera Darwin and Cloue Icefields (Tierra del Fuego) between 1945–2024 - Izagirre, Eñaut; Casassa, Gino; Dussaillant, Inés; Miles, Evan S.; Wilson, Ryan; Rada, Camilo; Faria, Sérgio H.; Antiguedad, Iñaki (Frontiers in Earth Science, 2025)
The rapid retreat of mountain glaciers due to climate change has led to the expansion of glacial lakes, which can produce sudden glacial lake outburst floods (GLOFs) due to the failure of unstable moraine or glacier dams, in some cases triggering a cascade of consequences. This study investigates the evolution of glacial lakes and the occurrence of GLOFs in the Cordillera Darwin and Cloue Icefields of Tierra del Fuego, southernmost South America, from 1945 to 2024 — a region that has not been analysed in detail before. Using historical aerial imagery, satellite data, UAV photogrammetry and field surveys, we document a 461% increase in the number of lakes (from 33 to 185) and a 124% increase in lake area (from 28.2 ± 5.6 to 63.3 ± 1.9 km2) as a result of glacier retreat. A pronounced shift from ice-dammed (71.6%–14.8% of the total area) to moraine-dammed lakes (80.5% by 2024) reflects the destabilisation of the ice margins and the exposure of overdeepened basins. We identified the first recorded southernmost GLOFs in this region, including a moraine collapse in 1997/98 that released ∼8.3 ± 1.2 × 106 m3 of water and a larger, adjacent cascading event in 2018 that released 28.3 × 106 m3 of water through successive moraine dam breaches. The cyclic outflows of the ice-dammed Lago Mateo Martinic (1985–2024) underline the dynamic interactions between ice and water. The results are consistent with global patterns of accelerated lake formation and growth over the last century, and with the diverse and complex processes at GLOFs that make Tierra del Fuego an important natural laboratory for studying the deglacierising environment. This study improves the understanding of glacial lake dynamics in the little-studied southern latitudes and emphasises the accelerated transformation of Andean cryospheric landscapes as warming progresses.